ScholarCitation: Chinese Scholar Citation Analysis Based on ScholarSpace in the Field of Computer Science - Su, Hanting; Fan, Zhuoya; Cao, Chen; Zhang, Yi; Wang, Shuo; Meng, Xiaofeng (Frontiers in Big Data, 2019)
Citation analysis is one of the most commonly used methods in academic assessments. Up to now, most of academic assessments are based on English literature, ignoring the fact that the role of Chinese papers in academic assessments has become increasingly indispensable. Therefore, to give full play to the role of Chinese literature in academic assessments is an urgent task of current academic circle. Based on Chinese academic data from ScholarSpace, i.e. 82826 Chinese computer science journal papers, we conduct a comprehensive assessment of academic influence from the perspectives of fields, journals and institutions, in order to achieve a better understanding of the development of Chinese computer literature in the past 60 years. We find that Chinese scholars tend to cite papers in English, discover evolution trend of fields, journals and institutions, and call on journals, institutions and scholars to strengthen their cooperation.